(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
Over the last decade, the domestic lighting market in Romania has been significantly transformed by the adoption of LED technology. Despite compliance with EU standards, LED product quality still varies, making it essential to evaluate their performance and impact on the power grid. This paper presents a detailed analysis of power quality (voltage and current harmonics) and electromagnetic interference in both common-mode and differential-mode, using time- and frequency-domain measurements of two commercially available LED drivers. The results indicate that, while LEDs offer substantial energy savings, some products generate notable harmonics and EMI, in certain cases exceeding recommended limits, highlighting the importance of careful product selection and characterization for reliable grid integration.